2018
DOI: 10.2147/ijn.s189505
|View full text |Cite
|
Sign up to set email alerts
|

Extended pain relief achieved by analgesic-eluting biodegradable nanofibers in the Nuss procedure: in vitro and in vivo studies

Abstract: BackgroundThe most common complaint after the Nuss procedure is severe postoperative chest pain. The aim of this study was to evaluate the effectiveness of analgesic-eluting biodegradable nanofibers in pain relief after the Nuss procedure.Materials and methodsPoly(d,l)-lactide-co-glycolide, lidocaine, and ketorolac were dissolved in 1,1,1,3,3,3-hexafluoro-2-propanol. This solution was electrospun into a nanofibrous membrane. The elution method and high-performance chromatography were used to characterize the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Lidocaine and ketorolac were employed as the analgesics. Figure 6D shows a photo of the electro-spun nanofibrous membranes, which had a thickness of approximately 0.12 mm and discharged sustained lidocaine and ketorolac for over 10 days, as shown in our previous study [22].…”
Section: Lidocaine and Ketorolac-eluting Nanofiberssupporting
confidence: 64%
See 2 more Smart Citations
“…Lidocaine and ketorolac were employed as the analgesics. Figure 6D shows a photo of the electro-spun nanofibrous membranes, which had a thickness of approximately 0.12 mm and discharged sustained lidocaine and ketorolac for over 10 days, as shown in our previous study [22].…”
Section: Lidocaine and Ketorolac-eluting Nanofiberssupporting
confidence: 64%
“…The degradation rate of PLGA is related to the LA:GA monomers' ratio, and the copolymer with 50:50 ratio exhibits the faster degradation (approximately 1-2 months) [19][20][21]. Our previous study incorporated analgesic-eluting nanofibers onto metallic Nuss bar and achieved the sustained and effective release of lidocaine and ketorolac for post-surgery pain relief for over 10 days (28.3 µg/mL and 17.8 µg/mL, respectively, for lidocaine and ketorolac at day 10) [22]. In addition, we used ethanol for the disinfection of PLA bars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, implants with 1.0 × 1.0 mm "windows" were capable of providing drug release over 25 days. A sustained release profile like this can be useful for local antimicrobial therapy or for pain management after surgery [46,47]. In these cases, a prolonged release over a period of a few weeks can be extremely beneficial to prevent infections or for pain management.…”
Section: In Vitro Drug Releasementioning
confidence: 99%
“…Thus, low MW PLGA are softer than common PLGA, which was well-known to be "stiff" (29,30). Several studies have reported biodegradable nanofiber membrane for the sustainable release of LDC significantly relieves the pain from surgical wounds or bone fractures in animal models (31)(32)(33). In our study, we set up the ratio of PLGA-to-LDC as a 1:1 mixture to facilitate higher amounts of LDC and more rapid drug release (33).…”
Section: Discussionmentioning
confidence: 99%